Initial yield and water use efficiency of fertirrigated sugarcane cultivars and plated by pre-sprouted seedlings - Coelho, Anderson Prates [UNESP]; Dalri, Alexandre Barcellos [UNESP]; Landell, Estêvão Pacheco de Andrade [UNESP]; De Faria, Rogério Teixeira [UNESP]; Palaretti, Luiz Fabiano [UNESP] (My University, 2018)
The increase in productivity of sugarcane goes through the adoption of new cultivation systems. Among them are the fertigation, use of cultivars adapted to production environments and the planting of pre-sprouted seedlings (PSS). Thus, this study aimed to evaluate the effect of fertigation on the initial productivity and water use efficiency (WUE) of five cultivars of sugarcane, as well as analyze the feasibility of harvest at 180 days after planting (DAP) using PSS. The cultivation was carried out under the management of supplementary irrigation and rainfed crop, with different doses of and potassium fertilization. The irrigation was triggered when there was a water deficit accumulated of 30 mm. The fertigation reduces the fertilizer doses (N and K2O) for sugarcane by 37.5% without affecting crop yield. The PSS planting increases the WUE of cultivars. From a productive point of view, it's advisable to cut at 180 DAP of sugarcane planted by PSS. The effect of irrigation on the yield of the cultivars was genotype-dependent, since the cultivar IAC 95-5000 under irrigation (117.86 t ha-1) showed higher productivity than the cultivation in the rainy season (84,41 t ha-1). On average, the irrigation increased sugarcane yield by 10.46%.
Produtividade inicial e eficiência no uso da água de cultivares de cana-de-açúcar fertirrigadas e plantadas por mudas pré-brotadas
Keywords: Early cycle; Seedlings; Supplementary irrigation; Water management